Xeroderma Pigmentosum With Early And Rapid Development Of Malignancy - Ghosh Arghyaprasum; Banerjee Raghubir; Coondoo Arijit (Wolters Kluwer Medknow Publications, 2000)
A case of xeroderma pigmentosum in a 9 year old developing multiple tumours over a short period of 6 months is reported. The tumours showed two different types of malignancies-squamous cell carcinoma and malignant melanoma. Two other siblings exhibited cutaneous lesions of xeroderma pigmentosum without any malignant change.